Mediating Effect of Job Satisfaction on the Relationship between Work-Life Balance and Job Performance among Academics: Data Screening - Wesarat, Phathara-on; Majid, H.; Sharif, M. Y.; Khaidir, Afriva; Susanto, Perengki (International Journal of Engineering and Technology, 2018)
This paper highlights the data screening for the research on mediating effect of job satisfaction on the relationship between work-life balance and job performance among full-time academics. It had 354 samples from the public universities located in Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT). The data screening procedure was applied to identify problematic patterns within the data set of the study. It analyzed the missing values, outliers, normality test, and multicollinearity test. The results of the data screening showed that the data was ready for further multivariate analysis.